FEATURES OF SUBPOPULATION COMPOSITION OF BLOOD LYMPHOCYTES IN RECIPIENTS WITHIN THE FIRST MONTH AFTER LIVER TRANSPLANTATION - A. N. Shoutko; O. A. Gerasimova; L. P. Ekimova; F. K. Zherebtsov; A. M. Granov (Вестник трансплантологии и искусственных органов)
Ratios of subpopulations of mononuclear blood cells in 68 patients were registered by method of flow cytometry during one month before or after transplantation of a cadaveric liver with the aim of a comparative assessment of the contribution of cellular factors into graft acceptance. Results. The obtained data allow considering the changes of separate Treg subpopulation after transplantation as a partial outcome of generalized shift of the whole process of lymphocytes differentiation, involving hematopoietic stem cells and prelymphocytes. This shift is followed by an increase of young hematopoietic stem cells, precursors of lymphocytes, angiogenic cells, and by a concomitant reduction of the majority of more matured subpopulations of lymphocytes. Conclusion. Diminishment of «tolerogenic» liver activity of before transplantation and its restoration after the organ’s replacement is explained by morphogenic/trophic mechanism. The basis of this mechanism is an increase in blood of hematopoietic stem cells and other cells transferring angiogenic and regenerative information to the graft.